Computerised design and simulation of meshing and contact of formate hypoid gears generated with a duplex helical method - Zhang, Yu (Strojniški vestnik, 2015)
The duplex helical method has higher machining efficiency for face-milling spiral bevel and hypoid gears. An accurate and practical approach for calculating the basic machine-tool settings of spiral bevel and hypoid gears manufactured with the duplex helical method is proposed in the present work. The gear tooth surface vector functions and curvature parameters based on basic machine, and head-cutter settings are calculated. Two types of curvature parameters for pinion tooth surfaces are obtained by utilizing the conjugation of gear and pinion tooth surfaces, and the conjugation of pinion tooth surfaces and pinion head-cutter surfaces at the reference point. Next, the basic machine settings for generating pinions in accordance with the two types of curvature parameters for pinion tooth surfaces are determined. Finally, a numerical examples using the duplex helical method are performed and validated by comparing with experimental results. New hypoid gear software has been developed using the new approach.
Keywords: čelno rezkanje; hipoidni zobniki; kontaktna analiza zob; metoda Duplex Helical; osnovne nastavitve stroja; parameter ukrivljenosti; posplošena teorija; referenčna točka; stožčasti zobniki